Lowering mortality risk in CR-HvKP infection in intestinal immunohistological and microbiota restoration - Hongyuhang Ni; Bill Kwan-Wai Chan; Lianwei Ye; Haoze Wu; Heng Heng; Qi Xu; Kaichao Chen; Rex Yan-Chu Cheung; Han Wang; Edward Wai-Chi Chan; Fuyong Li; Sheng Chen (Elsevier, 2024)
Gut damage during carbapenem-resistant and hypervirulent Klebsiella pneumoniae (CR-HvKP) infection is associated with a death risk. Understanding the mechanisms by which CR-HvKP causes intestinal damage and gut microbiota alteration, and the impact on immunity, is crucial for developing therapeutic strategies. This study investigated if gastrointestinal tract damage and disruption of gut microbiota induced by CR-HvKP infection undermined host immunity and facilitated multi-organ invasion of CR-HvKP; whether the therapeutic value of the rifampicin (RIF) and zidovudine (ZDV) combination was attributed to their ability to repair damages and restore host immunity was determined. A sepsis model was utilized to assess the intestinal pathological changes. Metagenomic analysis was performed to characterize the alteration of gut microbiota. The effects of the RIF and ZDV on suppressing inflammatory responses and improving immune functions and gut microbiota were evaluated by immunopathological and transcriptomic analyses. Rapid colonic damage occurred upon activation of the inflammation signaling pathways during lethal infections. Gut inflammation compromised host innate immunity and led to a significant decrease in probiotics abundance, including Bifidobacterium and Lactobacillus. Treatment with combination drugs significantly attenuated the inflammatory response, up-regulated immune cell differentiation signaling pathways, and promoted the abundance of Bifidobacterium (33.40 %). Consistently, supplementation of Bifidobacterium alone delayed the death in sepsis model. Gut inflammation and disrupted microbiota are key disease features of CR-HvKP infection but can be reversed by the RIF and ZDV drug combination. The finding that these drugs can restore host immunity through multiple mechanisms is novel and deserves further investigation of their clinical application potential.